Antibiotic consumption and resistance: a 3-years ecological study for four critical groups of bacteria in a general regional hospital - Sanjaya, Dwi Arymbhi; Siada, Nyoman Budiartha; Juanita, Rr Asih; Mahaputra, I Putu Yudistira; Kamalia, Made Gek Adisti; Meriyani, Herleeyana (Universitas Ahmad Dahlan, 2024)
Pseudomonas aeruginosa, Acinetobacter baumannii, Escherichia coli, and Klebsiella pneumoniae are the most critical groups of multi-drug resistant (MDR) bacteria that cause a threat in hospitals. This study identified the trend of antibiotic consumption, antibiotic resistance pattern, and the relationship between antibiotic consumption and antibiotic resistance in a critical group of bacteria in a general regional hospital. This ecological study was based on retrospective data from inpatient databases in a general regional hospital over three years (2017-2019). The trend for annual antibiotic consumption over 2017-2019 was defined as defined daily doses/100 bed-days. The relationship between total antibiotic consumption and the percentage of antibiotic resistance among four isolated critical bacteria was explored in time series analysis and linear regression. The most frequently used antibiotic was ampicillin (220.33 DDD/100 bed-days), ciprofloxacin (126.86 DDD/100 bed-days), and ampicillin-sulbactam (126.34 DDD/100 bed-days). There was a significant relationship between antibiotic consumption (ampicillin, ampicillin-sulbactam, ceftazidime, gentamicin, amikacin, and ciprofloxacin) in DDD/100 bed-days and antibiotic resistance in E. coli, K. pneumoniae, and P. aeruginosa (p<0.05) but not statically significant in A. baumannii (p=0.062). The annual usage fluctuated or remained stable, with no statistically significant trends change. The relationship between antibiotic consumption and antibiotic resistance was significant in three out of four critical groups of bacteria.